A model of manufacturing sector investment and employment decisions. - Lomax, J. W.; Bank of England (Bank of England, Economics Division, 1990)
This paper examines evidence for dynamic inter-relationships between firms' capital stock and employment decisions using co-integration techniques.
osc 08/04/2019
Loans
Keywords: Economics